2017
DOI: 10.1037/ort0000199
|View full text |Cite
|
Sign up to set email alerts
|

Student service members/veterans on campus: Challenges for reintegration.

Abstract: Many returning OIF/OEF/OND Veterans are seeking higher education in an effort to develop a meaningful career and financial stability. Evidence suggests that student service members/Veterans (SSM/Vs) are experiencing less academic success than other students. The purpose of this review is to identify the unique challenges of SSM/Vs and evaluate current campus efforts to facilitate their retention and academic performance. With a focus on SSM/Vs attending colleges and universities, we obtained 57 peer-reviewed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 48 publications
1
57
1
Order By: Relevance
“…Unfortunately, veterans may already view themselves as outsiders among their peers due to feelings of being misunderstood by traditional college students. According to Borsari et al (), veterans perceive themselves to be at a very different stage of life than traditional college students. The participants in our study reported similar feelings about their relationships with their peers.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, veterans may already view themselves as outsiders among their peers due to feelings of being misunderstood by traditional college students. According to Borsari et al (), veterans perceive themselves to be at a very different stage of life than traditional college students. The participants in our study reported similar feelings about their relationships with their peers.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, Hayden et al (2014) recommended developing and implementing psychoeducation groups with student veterans that focus on their identifying their interests, skills, and values. Colleges and universities can also support academic services such as student veteran–specific orientation courses (Borsari et al, 2017). Career counselors can be invited to these orientations to discuss student veterans’ career needs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cole (2013) suggested that academic advisors get to know SSM/V holistically to gain a sense of how their approaches and expectations within the academic setting have been shaped by their military experiences. Further, the increasing need for advisors and counselors to gain additional training to work with students who are experiencing PTSD, service-related disabilities, or other life-altering circumstances is suggested (Borsari et al, 2017;Cole, 2013;Spencer, 2016). For example, Schonfeld et al (2015), found that almost 30% of SSM/V identified difficulties in adjusting to college, and were more likely to report a history of mental health concerns during and after their military experiences.…”
Section: Implications For Student Affairs Professionals University Pementioning
confidence: 99%